The Impact of the Strategic Decision-Making on Firm Performance - Techaprasert, Nattana (2011)
The dissertation has examined the nature of strategic entrepreneurial decision-making process and how it influences firm performance. A secondary research method with case study analysis was used. An extensive literature review was performed to understand the nature of strategic decision-making approaches and processes. Two case studies of organizations were examined to understand how strategic entrepreneurial process was formed and implemented. The two case studies are the Renault-Nissan alliance and the second case was that of Vodafone market consolidation study. The case studies were examined for the nature of challenges that the firms faced and the methods used to overcome the challenges. The findings indicate that the strategic entrepreneurial decision-making process must be based on good quality of information and a structured process used to frame the objectives. The study also found that firms that pursue entrepreneurial strategy are more likely to have better performances. Some recommendations and suggestions for future research are also provided.